2012
DOI: 10.1136/annrheumdis-2012-eular.2972
|View full text |Cite
|
Sign up to set email alerts
|

SAT0024 Increased production of leukotrienes by peripheral blood mononuclear cells is associated with more severe disease and worse prognosis in patients with systemic sclerosis

Abstract: Background Leukotrienes (LTs) are a group of pro-inflammatory and pro-fibrotic, arachidonic acid-derived lipid mediators. We have shown that LTs are increased in the lungs of patients with interstitial lung disease (ILD) associated with systemic sclerosis (SSc). Objectives Since leukocytes are considered a major source of LTs in humans and since inflammatory infiltrates consisting of mononuclear cells are found in the skin and internal organs in early SSc, we undertook this study to investigate the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies performed in SSc revealed that neutrophils and mononuclear cells from the peripheral blood of SSc patients synthesize higher amounts of leukotrienes than cells obtained from healthy individuals [26,27]. In SSc patients, higher levels of LTB4 in the peripheral blood mononuclear cells (PBMC) cultures were associated with more severe disease as indicated by the presence of diffuse skin involvement, restrictive SSc-ILD, pulmonary hypertension, and greater vascular injury in capillaroscopy [28]. Moreover, higher concentrations of leukotrienes in PBMC cultures were associated with subsequent progression of the disease.…”
Section: Leukotrienes and Systemic Sclerosismentioning
confidence: 99%
“…Studies performed in SSc revealed that neutrophils and mononuclear cells from the peripheral blood of SSc patients synthesize higher amounts of leukotrienes than cells obtained from healthy individuals [26,27]. In SSc patients, higher levels of LTB4 in the peripheral blood mononuclear cells (PBMC) cultures were associated with more severe disease as indicated by the presence of diffuse skin involvement, restrictive SSc-ILD, pulmonary hypertension, and greater vascular injury in capillaroscopy [28]. Moreover, higher concentrations of leukotrienes in PBMC cultures were associated with subsequent progression of the disease.…”
Section: Leukotrienes and Systemic Sclerosismentioning
confidence: 99%